Biometric Identification: Face Recognition based on Iris Detection - Mohd Rizon, Mohamed Juhari, Prof. Madya Dr.; Tsuyoshi, Kawaguchi; R. Badlishah, Ahmad, Prof. Madya Dr.; Ahmad Nasir, Rosli (Kementerian Pengajian Tinggi Malaysia, 2010)
Prof. Madya Dr. Mohd Rizon Mohamed Juhari and his team won silver for Biometric Identification: Face Recognition based on Iris Detection at IPTA R&D Expo 2005, 30th September - 2nd October 2005. Organized by Ministry of Higher Education (MOHE) hosted by Universiti Teknologi Malaysia (UTM).